(untitled) (Research, Society and Development, 2021)
The addition of buttermilk powder as partial fat replacer in yogurt formulations with constant dry matter was investigated. Three formulations of yogurt were produced containing 0% (T1), 1.36% w·w-1 (T2) and 3.34% w·w-1 (T3) of buttermilk powder in the final product. Particle size and pH variation were monitored during fermentation; scanning electron microscopy and texture profile analysis were performed in the final product. The control sample showed larger particle size on the day after production and at the end of fermentation, as well as a more compact network microstructure with a smaller average pore size. Compared to the prototypes with added buttermilk the control sample showed greater higher firmness. Buttermilk powder could act as fat replacer for yogurt but favors the formation of a less compacted network microstructure, with large pores, less springiness after 21 days, and less hardness in the two evaluated times (21 and 42 days).